Web-based dental trauma database using Eden Baysal dental trauma index: a turkish multicenter study - Ece Eden; Burak Buldur; Gülsüm Duruk; Sibel Ezberci (European Oral Research)
Purpose To describe the prevalence and pattern of traumatic dental injuries (TDIs) among Turkish children in a web-based and multicenter design using Eden Baysal Dental Trauma Index (EBDTI). Materials and Methods The study sample consisted dental trauma patients aging 1-15 years and a webbased form was developed and used to record the information of the patients’ clinical and radiographic findings including EBDTI. The obtained data also included patient gender, age at the initial date of trauma, date of trauma, cause of injury and emergency treatment. Data were analyzed using Pearson Chi-square and Fisher's exact tests. Results A total of 280 traumatized teeth in 252 patients were evaluated. Dental trauma was seen more in boys and 7-10 years age group (p<0.05). There were significant differences between permanent and deciduous teeth with regard to uncomplicated and complicated crown fracture rate (p<0.05). The root fractures were mostly located at the apical third of the root in both dentitions. Conclusion TDI was associated with age, gender, and type of dental trauma. EDBTI provided easy and proper recording of multiple dental injuries and maturity of the apex and it was found to be a very useful tool to facilitate online recordings of dental injuries.